2017
DOI: 10.1097/bsd.0000000000000187
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of C-Arms for Intraoperative 3-dimensional Imaging and Navigation in Minimally Invasive Spine Surgery Part II

Abstract: 3D C-arms facilitate minimally invasive and accurate pedicle screw placement by providing 3D image datasets for intraoperative 3D imaging and navigation. However, the hereby potentially increased radiation exposure has to be considered. In particular, the Vision FD Vario 3D appears to generally evoke higher radiation exposures than the Siremobil Iso-C 3D. Well-indicated application of ionizing radiation and compliance with radiation protection principles remain mandatory to keep radiation exposure to patient a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 23 publications
0
22
0
3
Order By: Relevance
“…The surgical technique of performing minimally invasive stabilization procedures with screw-rod instrumentation (CD Horizon Sextant II or CD Horizon Longitude, Medtronic, Minneapolis, USA) has been described in detail elsewhere [ 14 ]. For minimally invasive thoracic instrumentation we routinely use intraoperative spinal navigation for accurate screw placement (Cart II system, Stryker, Freiburg, Germany; software: SpineMap 3D navigation) [ 15 , 16 ]. Usually, no drain was used in minimally invasive spine stabilization procedures.…”
Section: Methodsmentioning
confidence: 99%
“…The surgical technique of performing minimally invasive stabilization procedures with screw-rod instrumentation (CD Horizon Sextant II or CD Horizon Longitude, Medtronic, Minneapolis, USA) has been described in detail elsewhere [ 14 ]. For minimally invasive thoracic instrumentation we routinely use intraoperative spinal navigation for accurate screw placement (Cart II system, Stryker, Freiburg, Germany; software: SpineMap 3D navigation) [ 15 , 16 ]. Usually, no drain was used in minimally invasive spine stabilization procedures.…”
Section: Methodsmentioning
confidence: 99%
“…8 Los equipos de última generación podrían suponer que el producto emite menos radiación que los antiguos, pero en Alemania, se compararon dos sistemas: SiremobilIso-C 3D y Vision FD Vario 3D, y se comprobaron exposiciones a la radiación numéricamente más altas con el Vision FD Vario 3D que con el SiremobilIso-C 3D, esta última es más antigua que la primera y, como era de esperar, la exposición a la radiación es más alta para la glándula tiroides en las exploraciones 3D cervicales. 10 Por otro lado, se informó que los delantales plomados reducían la dosis efectiva 16 veces para el cirujano. 10 En China, en un gesto para disminuir el riesgo de exposición a la radiación, se utilizó el prototipado rápido asistido por computadora, que consiste en simular una operación por computadora utilizando un esquema de diseño y planificación quirúrgicos que muestra los resultados del procedimiento, en el que se realiza la cirugía virtual y se definen la ubicación, el diámetro, la dirección de profundidad de los tornillos pediculares y así se evitan los órganos neurovasculares y se asegura la correcta colocación de los tornillos pediculares diseñados.…”
Section: Discussionunclassified
“…10 Por otro lado, se informó que los delantales plomados reducían la dosis efectiva 16 veces para el cirujano. 10 En China, en un gesto para disminuir el riesgo de exposición a la radiación, se utilizó el prototipado rápido asistido por computadora, que consiste en simular una operación por computadora utilizando un esquema de diseño y planificación quirúrgicos que muestra los resultados del procedimiento, en el que se realiza la cirugía virtual y se definen la ubicación, el diámetro, la dirección de profundidad de los tornillos pediculares y así se evitan los órganos neurovasculares y se asegura la correcta colocación de los tornillos pediculares diseñados. 11 En un estudio comparativo de descompresión posterior mínimamente invasiva combinada con la fijación de tornillos pediculares percutáneos y la cirugía posterior abierta para tratar fracturas toracolumbares, se observó que la exposición a la radiación y el tiempo operatorio fueron mayores en el primer grupo.…”
Section: Discussionunclassified
“…Since 3D imaging systems were introduced into the orthopaedic OR, their feasibility in spine surgery has been examined. The first reports on the use of these systems to control the result intra‐operatively for spinal procedures were found in 2008, and to date, to most surgeons, the image quality of the intra‐operatively acquired images and the intra‐operative emission of radiation are the major limitations . Therefore, new technological developments should address these concerns and need to be systematically evaluated regarding these parameters, especially since recent studies have revealed a reduced rate of screw revisions with intra‐operative 3D imaging .…”
Section: Discussionmentioning
confidence: 99%